2015
DOI: 10.1111/coa.12309
|View full text |Cite
|
Sign up to set email alerts
|

Elective neck dissection during salvage total laryngectomy – a beneficial prognostic effect in locally advanced recurrent tumours

Abstract: Elective neck dissection during salvage total laryngectomy seems to improve survival in patients with advanced local disease at recurrence. The role of neck dissection in the treatment of smaller tumours awaits further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 14 publications
2
36
1
2
Order By: Relevance
“…Of the four included studies with these data, only one of 14 patients with a regional recurrence after an observed neck had long‐term survival (5‐year OS = 7%) . Other included studies showed equivalent rates of regional recurrence between END and observed necks, or even greater rates in END patients, without report of their survival …”
Section: Discussionmentioning
confidence: 99%
“…Of the four included studies with these data, only one of 14 patients with a regional recurrence after an observed neck had long‐term survival (5‐year OS = 7%) . Other included studies showed equivalent rates of regional recurrence between END and observed necks, or even greater rates in END patients, without report of their survival …”
Section: Discussionmentioning
confidence: 99%
“…They performed 42 ipsilateral NDs and 9 bilateral NDs and found no occult nodal metastases in the contralateral neck, similarly no contralateral neck disease was found in a recently published cohort . A total of 3 studies reported occult nodal metastases in hemidissected necks (unilateral and bilateral NDs), however, did not comment on whether they occurred in the contralateral neck. Pennings et al reported results based on patients who had lymph nodes at levels II and III visually and manually inspected intraoperatively; any suspicious lymph nodes were removed by selective upper node dissection, and if either inspection or dissection was positive for neck metastases a modified radical ND of levels I‐V was performed on the affected side .…”
Section: Discussionmentioning
confidence: 85%
“…In 3 studies, END appears to offer increased DFS over no ND, especially in the situation of late T classification at recurrence . However, there was no significant difference in pooled 5‐year DFS between those who received END and those who had no ND (OR = 0.76, CI = 0.49‐1.17, P = 0.21, I 2 = 10%; summarized in Figure ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations